2016
DOI: 10.1111/nmo.12842
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between mast cells, enterochromaffin cells, and sensory signaling in the aging human bowel

Abstract: BackgroundAdvanced age is associated with a reduction in clinical visceral pain perception. However, the underlying mechanisms remain largely unknown. Previous studies have suggested that an abnormal interplay between mast cells, enterochromaffin (EC) cells, and afferent nerves contribute to nociception in gastrointestinal disorders. The aim of this study was to investigate how aging affects afferent sensitivity and neuro‐immune association in the human bowel.MethodsMechanical and chemical sensitivity of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 42 publications
0
36
0
1
Order By: Relevance
“…Firstly, whilst every effort was made to match the relative age range and sex of the NMR and mice used in this study, we acknowledge that age may have an impact on afferent sensitivity. For example, reduced responses of afferent firing to some stimuli are observed in tissues from older mice [44] and humans [45,46]. We accept that this may have introduced variability into our study, but given the relatively comparable spread in age of the individuals used from both species, we do not believe that this is responsible for the dramatic differences observed between species.…”
Section: Discussionmentioning
confidence: 88%
“…Firstly, whilst every effort was made to match the relative age range and sex of the NMR and mice used in this study, we acknowledge that age may have an impact on afferent sensitivity. For example, reduced responses of afferent firing to some stimuli are observed in tissues from older mice [44] and humans [45,46]. We accept that this may have introduced variability into our study, but given the relatively comparable spread in age of the individuals used from both species, we do not believe that this is responsible for the dramatic differences observed between species.…”
Section: Discussionmentioning
confidence: 88%
“…For example, reduced responses of afferent firing to some stimuli are observed in tissues from older mice 44 and humans. 45,46 We accept that this may have introduced variability into our study, but given the relatively comparable spread in age of the individuals used from both species, we do not believe that this is responsible for the dramatic differences observed between species. Secondly, all NMR used in this study were subordinates and therefore their sexual maturity will have been suppressed.…”
Section: Discussionmentioning
confidence: 92%
“…Several animal studies have indicated that the mechanical stimulus threshold can be decreased upon chemical activation with mustard oil. These findings have recently been confirmed in an ex vivo study using human colonic tissue . Moreover, TRPA1 can be sensitized via PAR 2 activation.…”
Section: Trpa1mentioning
confidence: 86%